Implementasi Model Pembelajaran Berbasis Proyek dalam Meningkatkan Keterampilan Berfikir Siswa - Fazillah, Oryn; Nisa, Sahrun (MASALIQ, 2024)
This research aims to find out how the implementation of a project-based learning model can improve students' thinking skills. The use of a project-based learning model is an effective way to develop critical, analytical and creative thinking skills in students. In this model, students are given project assignments that must be completed in groups by following scientific stages starting from formulating problems, designing problem solutions, implementing plans, to presenting the final results. Through the process of completing the project, students are trained to identify problems, collect and analyze data, formulate hypotheses, plan experiments, draw conclusions, and communicate results. Direct student involvement in each stage will encourage them to think critically, creatively and analytically in solving real problems. This research uses qualitative methods with observation, interview and document study techniques to collect data. The research results show that the implementation of a project-based learning model can improve students' thinking skills significantly. Students become more active, enthusiastic and motivated in the learning process, and are able to develop the higher order thinking skills needed in the 21st century.